The economic efficiency of the use of methods of basic tillage in technology of sunflower growing - Компанієць, В. О.; Кулик, А. О.; Кохан, А. В. (Scientific Progress & Innovations, 2016)
The economic evaluation of results of experimental researches on determination of efficiency of different methods of basic soil tillage in technology of sunflower growing in soil and climatic conditions of northern Steppe of Ukraine was made. The researches were conducted on the basis of the State enterprise of experimental farm «Dnipro» of Institute of cereals cultures NAAS. According to results of comprehensive evaluation we formulated recommendations for improving productivity and profitability of production of sunflower seeds on the basis of the most effective methods of basic tillage.